Decentralized subject indexing of television programs: The effects of using a semicontrolled indexing language. (13th June 2016) - Søbak, Veslemøy; Pharo, Nils
Abstract : We performed an exploratory case study to understand how subject indexing performed by television production staff using a semicontrolled vocabulary affects indexing quality. In the study we used triangulation, combining tag analysis and semistructured interviews, with production staff of the Norwegian Broadcasting Corporation. The main findings reveal incomplete indexing of TV programs and their parts, in addition to low indexing consistency and uneven indexing exhaustivity. The informants expressed low motivation and a high level of uncertainty regarding the task. Internal guidelines and high domain knowledge among the indexers does not form a sufficient basis for creating quality and consistency in the vocabulary. The challenges that are revealed in the terminological analysis, combined with low indexing knowledge and lack of motivation, will create difficulties in the retrieval phase.